African Food Systems Transformation Brief 06: The Status of Food Storage, Transport and Logistics Infrastructure in Africa - George Mark Onyango; Robert Bitariho; Naomi Kandawini (African Food Systems Transformation Collective. Cape Town, South Africa, 2025)
Food systems are critical to many African economies but face significant challenges due to underdeveloped or non-existent food storage, transport and trade infrastructures. This results in high post-harvest losses, inefficient supply chains, health hazards and limited market access for farmers – problems worsened by climate change. Integrating storage, transport and trade practices through agroecological transitions can enhance food security, reduce waste and support sustainable food systems, which would align them with sustainable development goals (SDGs). Smallholder farmers in rural areas rely on efficient local storage, intermediate transport and simple logistics systems to access markets, generate income, and improve livelihoods. Agroecological transitions empower farmers, boost productivity and promote economic growth. Climate-resilient practices, such as agroforestry and crop diversification, enhance resilience to climate shocks. These transitions also emphasise social equity by empowering local communities, preserving indigenous knowledge systems, and resolving poverty, inequality and land-tenure issues. Agroecological transitions in Sub-Saharan Africa – particularly in Uganda, Kenya and Ghana – should focus on food-storage improvements, efficient transportation networks and sustainable trade infrastructures. Food storage improvements aim to increase food security and reduce food waste. Food transportation focuses on efficient distribution networks based on intermediate transport that reduces emissions and connects local producers with markets. Stakeholders all play vital roles in the supply chain; they include government bodies, private-sector companies, non-governmental organisations (NGOs), farmers, transporters, academics, researchers, and traders. Efficient local infrastructure enhances productivity, food security and public health. Investments in modernising storage facilities respond to challenges such as outdated technology and climate impacts. Collaborations among governments, the private sector, and local communities reduce post-harvest losses and strengthen local food security. Philanthropic support for local infrastructure aligns wellwith the goals of alleviating hunger, reducing poverty, improving health, promoting sustainability and advancing social equity. Investments in intermediate transport facilities (motorbikes, ‘tuk-tuks’ and bicycle taxis) and community storage infrastructure such as granaries and warehouses can lead to transformative changes, which improve lives and set a model for sustainable development.
The Status of Food Storage, Transport and Logistics Infrastructure in Africa: Experiences from Uganda, Kenya and Ghana
Keywords: Food systems; Food Storage; Transport and Logistics Infrastructure; HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::African and comparative archaelogy